Răspuns :
{6×[6+(a×6)]:2}×4=366-6
{6×[6+(a+6)]:2}×4=360
6×[6+(a+6)]:2=360:4
6×[6+(a+6)]:2=90
3×[6+(a+6)]=90
6+(a+6)=90:3
6+(a+6)=30
a+12=30
a=30-12
a=18
{6×[6+(a+6)]:2}×4=360
6×[6+(a+6)]:2=360:4
6×[6+(a+6)]:2=90
3×[6+(a+6)]=90
6+(a+6)=90:3
6+(a+6)=30
a+12=30
a=30-12
a=18
6 + { 6 x [ 6 + ( a x 6 ) ] : 2 } x 4 = 366
{ 6 x [ 6 + ( a x 6 ) ] : 2 } x 4 = 366 - 6
{ 6 x [ 6 + ( a x 6 ) ] : 2 } x 4 = 360
6 x [ 6 + ( a x 6 ) ] : 2 = 360 : 4
6 x [ 6 + ( a x 6 ) ] : 2 = 90
6 x [ 6 + ( a x 6 ) ] = 90 × 2
6 x [ 6 + ( a x 6 ) ] = 180
6 + ( a x 6 ) = 180 : 6
6 + ( a x 6) = 30
a x 6 = 30 - 6
a = 24 : 6
a = 4